A longer duration of estrogen deficiency increases fibrosis risk among postmenopausal women with nonalcoholic fatty liver disease. Issue 1 (5th April 2016) - Klair, Jagpal Singh; Yang, Ju Dong; Abdelmalek, Manal F.; Guy, Cynthia D.; Gill, Ryan M.; Yates, Katherine; Unalp‐Arida, Aynur; Lavine, Joel E.; Clark, Jeanne M.; Diehl, Anna Mae; Suzuki, Ayako; ,
Abstract : Postmenopausal women with nonalcoholic steatohepatitis are at an increased risk of hepatic fibrosis compared with premenopausal women. Whether duration of estrogen deficiency in postmenopausal state dictates an individual's fibrosis risk remains uninvestigated. We assessed the associations of age at menopause and time from menopause with fibrosis severity in postmenopausal women with nonalcoholic fatty liver disease. Data from 488 postmenopausal women with (1) histologic diagnosis of nonalcoholic fatty liver disease and (2) self‐reported information on age at menopause were analyzed. The associations of premature menopause (age at menopause of <40 years) and time from menopause (age at study enrollment ‐ age at menopause, years) with fibrosis severity (stage 0‐4) were assessed using multiple ordinal logistic regression models with and without adjusting for clinical confounders. Among the participants (age at menopause 43.7 ± 8.6 years), women with premature menopause (29.3%) were younger at enrollment ( P < 0.001) and used hormone replacement therapy more often ( P < 0.003). After adjusting for age at enrollment, race, waist circumference standardized by body mass index, current smoking, current alcohol use, hypertension, diabetes/impaired fasting glucose, homeostatic model assessment of insulin resistance, and hormone replacement therapy, premature menopause was associated with an increased likelihood of having more severe fibrosis (adjusted cumulative odds ratio = 1.9, 95% confidence interval 1.3‐2.7, P = 0.001), while time from menopause was directly associated with an increased likelihood of having more severe fibrosis (adjusted cumulative odds ratio for 5‐year unit = 1.2, 95% confidence interval 1.1‐1.3, P = 0.002). Conclusion : Duration of estrogen deficiency in postmenopausal state confers fibrosis risk among postmenopausal women with nonalcoholic fatty liver disease. (Hepatology 2016;64:85–91)